TYPE 3 DIABETES: THE MOLECULAR LINK BETWEEN INSULIN RESISTANCE AND NEURODEGENERATION (Ustozlar uchun, 2026)
Type 3 diabetes (T3D) is a proposed term for Alzheimer’s Disease (AD) that represents a form of diabetes that selectively involves the brain. This condition is characterized by brain-specific insulin resistance and insulin deficiency, which triggers a cascade of neurodegenerative processes. This review explores the pathophysiology, clinical presentation, and emerging therapeutic landscape for T3D.